Modelagem e simulação de células a combustível de etanol direto - Maia, Leonardo Kenji Komay (2016)
Two mathematical models of a Direct Ethanol Fuel Cell (DEFC) considering both an ideal (complete ethanol oxidation) and a realistic behavior (partial oxidation with by-products) were implemented in 3D geometries, adapted from SOUSA et al. (2008), using ANSYS CFX. The ideal model considers the cleavage of the C-C bond in the ethanol molecule, leading to a complete oxidation with CO2 and water as products, whereas the realistic model leads to partially oxidized products (acetic acid and acetaldehyde) through a dissociative adsorption mechanism on the catalyst surface. Kinetic parameters of the realistic model were readjusted from the original work (SOUSA et al., 2008) by experimental data fitting in order to calculate surface coverages of the adsorbed species. Model assumptions are: laminar flow, steady-state, isothermal, homogeneous and isotropic porous materials. Analysis of velocity, pressure and concentration profiles were performed in five different anode flow designs: serpentine, double serpentine, parallel, interdigitated and spot. Results have shown that, within the anode flow designs evaluated, the DEFC containing the interdigitated design presented a better performance, measured by the current density vs. cell potential curve. Cell performance was evaluated between anode overpotentials of 0 to 0,5 V. Different inlet velocities were tested to assess how the solution permeates through the porous layers. A qualitative analysis was also performed with a non-isothermal ideal DEFC model to investigate how each anode flow design contributes to heat removal in the fuel cell. Results showed that heat was better removed in the double serpentine and serpentine anode flow designs.